Muscle power and velocity during trunk rotations after 6 weeks of training in ice-hockey players - Poór, O.; Glevanák, D.; Zemková, E. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2017)
The study evaluates changes of muscle power and velocity during trunk rotations in ice-hockey players after six weeks of training in competition period. A group of 15 ice-hockey players performed 2 trunk rotations to each direction in a standing position with barbell of 6, 10, 12, 16, 20, 22, 26 kg placed on the shoulders. Basic biomechanical parameters during the movement were monitored using the FiTRO Torso Dyne system. Results showed that mean velocity in acceleration phase of trunk rotation significantly increased after 6 weeks of training at 6 kg (from 259 to 282.6 deg/s, p = 0.003) and 12 kg (from 218.8 to 244.1 deg/s p = 0.004). However, its values did not changed significantly during rotations with 10, 16, 20, 22 and 26 kg. Mean power of trunk rotation did not changed significantly with any of used weight. These findings indicate that there are only small changes in muscle power in competition period of ice hockey-players.